ANALYSIS OF JUNIOR HIGH SCHOOL SCIENCE STUDENT BOOK ON CURRICULUM 2013 - Fradina Novita Anggraini; Finda Nur Oktavia; Darul Hikmah (Universitas Negeri Surabaya, 2021)
Science subjects in junior high school/madrasah tsnawiyah aim to make students have various abilities. Science learning plays a vital role in the educational process and technological developments. This research is a descriptive type of research, using a qualitative approach, namely by analyzing the student's science books for the curriculum 2013 of VIII class at junior high school/Madrasah Tsnawiyah. The analysis results obtained from the eighth-grade student book consisted of five aspects. The first is the suitability of the content of the book with the scope of basic competence (i.e., KD), the second aspect is the breadth, depth, currentness, and accuracy of the learning material in each chapter, the third aspect show examples of learning material (factual, conceptual, and procedural knowledge) in each chapter of the student book, the fourth aspect is the feasibility of the activity learning in each student book chapter, and the last element of the feasibility of assessing each chapter of the student book.